Partial embolization as re-treatment of hypersplenism after unsuccessful splenic artery ligation - Xu, Zheng-Ju (World J Gastroenterol, 2015)
Ligation of splenic artery (LSA) is used for the treatment of liver cirrhosis with hypersplenism. However, hypersplenism is not significantly improved following LSA treatment in some cases, and there are few reports of retreatment of hypersplenism after LSA. We report the case of a 47-year-old man with liver cirrhosis and hypersplenism who underwent LSA treatment, but did not significantly improve. Laboratory tests revealed severe leukocytopenia and thrombocytopenia. Celiac computed tomography arteriogram and digital subtraction angiography revealed two compensatory arteries connected to the hilar splenic artery from the left gastro-epiploic artery and from the dorsal pancreatic artery. Partial splenic embolization (PSE) was performed through the compensatory arteries. As a result, the patient achieved partial splenic ischemic infarction, and white blood cell and platelet counts rose and remained in the normal range. PSE is an effective therapeutic modality for the retreatment of hypersplenism when other modalities have failed.